“Caroline” and the Mountain: Popular Children’s Picture Books that Shape the Perception of the Mountain - Christophe Meunier (Revue de Géographie Alpine)
Caroline, whom author Pierre Probst created in 1953, is a very popular character in French children’s literature. In the 44 picture books that comprise the series dedicated to her, she takes readers around different areas: domestic and distant, urban and rural, maritime and mountainous. Probst’s picture books depict characters evolving in converted landscapes as they frequent inhabited territories. Caroline aux sports d’hiver (1959), the seventh part in the series, was published when winter mountain tourism started to become popular. And for its part, Caroline fait du cheval (1989), the 22nd book in the series, presented summer mountain tourism just as it was becoming popular. These two picture books, despite being situated in a particular temporality and spatiality, have been republished and translated many times over. This article seeks to show how the two works can be considered as geographical and cultural products and to study the iconotextual processes that make it possible to build mountain areas and to provide practical examples, which I shall call spatiality.